Cyber Fatwa and Da'wah Acceptance in New Media: How Technology Affects Religious Message by Female Ulama - Imam Subchi; Kusmana Kusmana; Zulkifli Zulkifli; Dewi Khairani; Rena Latifah (Universitas Islam Negeri Jakarta, 2022)
Through religious activities in cyberspace, new media has become one of the enabling reasons for the emergence of female ulama. It has created a channel for them to exhibit their identity and compete as religious preachers. Numerous Islamic studies organizations and societies have developed on social media, along with religious leaders who use the platform to disseminate Islamic learning activities across various social media channels, increasingly highlighting the signals of religious populism. This study employs a quantitative approach to assess female ulama's acceptance of new media by distributing online questionnaires to Islamic University civitas academia. The research model comprises eleven potential relationship paths based on the Technology Acceptance Model theory. There haven't been many studies on the acceptance of technology in religious affairs in Indonesia. An important finding is that the respondents' social influence does not affect the use of new media to access the female ulama lecture. The popularity of female scholars in presenting religious messages through modern media is currently acceptable. This study concludes that even in a homogeneous atmosphere, the female ulama remains unpopular; this may be attributed to the female scholar's continued use of the traditional approach in her lectures. Based on the result, a modern approach to delivering a religious message is needed to solve the issue and improve da'wah's impact and a cyber fatwa by female ulama in contemporary Indonesia. Abstrak:Melalui aktivitas keagamaan di dunia maya, media baru menjadi salah satu alasan yang memungkinkan munculnya ulama perempuan dan telah menciptakan saluran bagi mereka untuk menunjukkan identitasnya dan bersaing sebagai pendakwah. Banyak organisasi dan masyarakat pengkaji Islam telah berkembang di media sosial, bersama dengan para pemimpin agama yang menggunakan platform untuk menyebarluaskan kegiatan pembelajaran Islam di berbagai saluran media sosial, semakin menyoroti sinyal populisme agama. Penelitian ini menggunakan pendekatan kuantitatif untuk menilai penerimaan ulama perempuan terhadap media baru dengan menyebarkan kuesioner online kepada civitas akademika Universitas Islam. Model penelitian ini terdiri dari sebelas jalur hipotesa berdasarkan teori Technology Acceptance Model (TAM). Belum banyak penelitian tentang penerimaan teknologi dalam urusan keagamaan di Indonesia. Temuan penelitian ini adalah bahwa pengaruh sosial dari responden ini tidak mempengaruhi penggunaan media baru untuk mengakses ceramah ulama perempuan. Popularitas ulama perempuan dalam menyampaikan pesan-pesan keagamaan melalui media modern saat ini dapat diterima. Studi ini menyimpulkan bahwa bahkan dalam suasana homogen, ulama perempuan tetap tidak populer; ini mungkin disebabkan oleh penggunaan pendekatan tradisional yang terus menerus oleh cendekiawan perempuan dalam penyampaian dakwah dan fatwanya. Berdasarkan hasil tersebut, diperlukan pendekatan modern dalam penyampaian pesan agama untuk memperbaiki situasi dan meningkatkan dampak dakwah dan fatwa siber oleh ulama perempuan di Indonesia saat ini.